OPTIMIZATION OF SIMP (SOLIDITY, INTEGRITY, MENTALITY, PROFESSIONALITY) ELECTION SUPERVISORS TO ACHIEVE DEMOCRATIC, HONEST AND FAIR ELECTIONS - Muhammad Asmawi; Lathifah Sandra Devi (JHR (Jurnal Hukum Replik), 2023)
A democratic country is a country whose government is run based on the principle of popular sovereignty. Popular sovereignty means that the people have the ultimate power to determine state policies and regulations. The people can use this power in various ways, such as elections, referendums, and petitions. The purpose of this writing is to maximize the performance of general election supervisors to realize democratic, honest and fair general elections. The research method uses descriptive qualitative analysis using data taken from literature sources and then analyzed. The results of the study that as election organizers must have an attitude of solidarity, integrity, mentality and professionalism. The responsibility of the election supervisor is the Election Supervisory Body (Bawaslu). Bawaslu as an institution responsible for implementing general elections is obliged to improve the loyalty, performance and behavior of election supervisors in order to achieve democratic, honest and fair general elections. Optimizing the behavior of election supervisors to improve integrity can be done with technical guidance, consolidation between election administrators and digitalization of supervisory applications